Impact of the REACT Learning Model on Students Activity and Academic Performance - Suci Hapizah; Ernawati Ernawati; Dedi Hermon (Postgraduate, University of Mataram, 2025)
Student participation and achievement in geography learning are often low due to limited use of contextual learning approaches. This study aimed to improve students learning activity and academic performance in Geography among tenth-grade students at Senior High School 1 Kampar through the REACT (Relating, Experiencing, Applying, Cooperating, Transferring) learning model. The study employed a classroom action research design conducted in three cycles, each consisting of planning, implementation, observation, and reflection. The participants were 38 students in the 2024/2025 academic year. Data were collected through observation sheets and achievement tests and analyzed descriptively with a paired sample t-test. The findings showed that student activity scores increased from 64.2 in Cycle I to 88.4 in Cycle III, and learning outcomes improved from 67.5 to 89.6, with significant differences across cycles (p < 0.05). These results demonstrate that the REACT model effectively enhances students’ engagement and academic performance. The implication of this study is that the REACT model can serve as an effective pedagogical strategy to promote active, contextual, and meaningful learning in geography education and other related disciplines